White matter integrity mediates the associations between white matter hyperintensities and cognitive function in patients with silent cerebrovascular diseases. (22nd November 2022) - Chen, Jing; Ge, Anyan; Zhou, Ying; Ma, Yuanyuan; Zhong, Shaoping; Chen, Caizhong; Shi, Weibin; Ding, Jing; Wang, Xin
Abstract: Objective: To evaluate the relationships between cognitive function and white matter hyperintensity volume (WMHV) in patients with silent cerebrovascular disease and to investigate whether white matter integrity or brain atrophy play a role in this association. Methods: Automated Fiber Quantification and Voxel‐ based morphometry were used to track and identify the integrity of 20 well‐defined white matter tracts and to measure the gray matter volume (GMV). A linear regression model was applied for examining the associations between cognitive function and WMHV and mediation analysis was used to identify the roles of white matter integrity or GMV in the influence of WMHV on cognitive function. Results: Two hundred and thirty‐six individuals were included for analysis. Executive function was linearly associated with fractional anisotropy (FA) of the right interior frontal occipital fasciculus (IFOF) ( β  = 0.193; 95% CI, 0.126 to 1.218) and with WMHV ( β  = −0.188; 95% CI, −0.372 to −0.037). Information processing speed was linearly associated with WMHV ( β  = −0.357; 95% CI, −0.643 to −0.245), FA of the right anterior thalamic radiation (ATR) ( β  = 0.207; 95% CI, 0.116 to 0.920), and FA of the left superior longitudinal fasciculus (SLF) ( β  = 0.177; 95% CI, 0.103 to 1.315). The relationship between WMHV and executive function was mediated by FA of the right IFOF (effect size = −0.045, 95% CI, −0.015 to −0.092). Parallel mediation analysis showed that the association between WMHV and information processing speed was mediated by FA of the right ATR (effect size = −0.099, 95% CI, −0.198 to −0.038) and FA of the left SLF (effect size = −0.038, 95% CI, −0.080 to −0.003). Conclusion: These findings suggest a mechanism by which WMH affects executive function and information processing speed by impairing white matter integrity. This may be helpful in providing a theoretical basis for rehabilitation strategies of cognitive function in patients with silent cerebrovascular diseases. Abstract : These findings may provide an underlying mechanism that white matter hyperintensities affects executive function and information processing speed via impairing the white matter integrity. It may be helpful in providing theoretical basis for rehabilitation strategies of cognitive function in patients with silent cerebrovascular diseases.